2017
DOI: 10.1080/14786419.2017.1343327
|View full text |Cite
|
Sign up to set email alerts
|

A new ent-kaurane diterpene derivative from the stems of Eurya chinensis R.Br

Abstract: One new ent-kaurane diterpene derivative (1), along with four known diterpenes, was isolated from the stems of Eurya chinensis R.Br. The structure of the new compound was established by extensive analysis of mass spectrometric and 1D and 2D NMR spectroscopic data. Compound 1 showed moderate anti-inflammatory activities with IC value of 8.12 μM. This is the first example of diterpenoids with 4-hydroxy-4-(2-hydroxyethyl)-1-hydroxyl-cyclohexanoyl substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The subfractions were subjected to silica gel (200–300 mesh, Qingdao Marine Chemical Inc., Qingdao, China), Sephadex LH-20 gel (CHP20P, 75–150 μm, Mitsubishi Chemical Industries Ltd, Tokyo, Japan), C18 reversed-phase silica gel (150–200 mesh, Merck, Darmstadt, Germany) column chromatography to obtain the pure compounds by following similar procedures as we described previously (J. Song et al, 2018a , 2018b ) with minor modification. 1D and 2D NMR spectra were recorded on a Bruker Advance-500 spectrometer with TMS as internal standard (Bruker BioSpin AG, Fallanden, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subfractions were subjected to silica gel (200–300 mesh, Qingdao Marine Chemical Inc., Qingdao, China), Sephadex LH-20 gel (CHP20P, 75–150 μm, Mitsubishi Chemical Industries Ltd, Tokyo, Japan), C18 reversed-phase silica gel (150–200 mesh, Merck, Darmstadt, Germany) column chromatography to obtain the pure compounds by following similar procedures as we described previously (J. Song et al, 2018a , 2018b ) with minor modification. 1D and 2D NMR spectra were recorded on a Bruker Advance-500 spectrometer with TMS as internal standard (Bruker BioSpin AG, Fallanden, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Our group previously found that the main chemical constituents of E. chinensis stems include mainly terpenoids, coumarins and flavonoids (J. Song et al, 2018a , 2018b ) possessing anti-inflammatory and antibacterial activity (J. L. Song et al, 2017 ). However, there are no reports on the chemical profile and efficacy of its leaves, which were widely used as “Dagang Tea” for clinical care and the treatment of fever and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Using scales of 100 μmol of diterpenoid instead of 20 mmol, the reaction yielded (4S,8S)-15,16-epoxy-8,17-dihydroxy-13(16),14-ent-labdadien-18-oic acid (1c), a previously undescribed compound, and the known compound 16α,17-dihydroxy-ent-kauran-19-oic acid (2c). Whereas the latter compound was identified by comparison of MS and NMR spectra to literature data (Song et al 2018), structure elucidation of compound 1c is described in "Structure Elucidation and Configuration of Compound 1c".…”
Section: Dihydroxy Derivativesmentioning
confidence: 99%
“…It was reported that inflammation-related signaling pathways might be affected in the liver tissues of mice treated with E. chinensis extract [13]. Recently, phytochemistry studies on the E. chinensis started to afford a series of novel diterpenes which have been proved to possess promising anti-inflammatory activities [14][15][16]. However, as a great potential phytomedicine, the investigations of its phytochemical and pharmacological properties are still scarce, and the scientific basis for liver protection of this plant has never been reported.…”
Section: Introductionmentioning
confidence: 99%